Determinants of influenza and pertussis vaccine uptake in pregnant women in Ireland: A cross-sectional survey in 2017/18 influenza season. Issue 43 (8th October 2019) - Quattrocchi, A.; Mereckiene, J.; Fitzgerald, M.; Cotter, S.
Highlights: Influenza and pertussis vaccine uptake is moderate in pregnant women in Ireland. Vaccines uptake increases with awareness of campaign and by socio-economic status. General practitioners are the primary source for vaccine recommendation. Multifaceted campaigns should target population in all socio-economic groups. Omnibus surveys represent a timely and cost-saving method to reach specific target groups. Abstract: In Ireland seasonal influenza and pertussis vaccination during pregnancy is recommended and every year national campaigns are organised to raise awareness and improve uptake. We estimated influenza and pertussis vaccine uptake and identified factors associated with vaccination status in pregnant women in 2017/18. We conducted a face-to-face omnibus survey, with quota sampling, among women aged 18–55 years and collected socio-demographic characteristics, self-reported vaccination status, awareness of vaccine campaigns, and attitudes towards vaccination. Sample was weighted to ensure representativeness with the target population. We performed univariate and multivariable logistic regression analyses on survey data. Overall, 241 pregnant women were enrolled. Influenza and pertussis vaccine uptake was 61.7% and 49.9%, respectively. Awareness of vaccine campaign and socio-economic status (SES) were associated with both influenza and pertussis vaccine uptake. The association between SES and uptake of vaccines differed by awareness. Women aware of the influenza vaccine campaign and with mid and low SES were less likely to be vaccinated, compared to those with high SES (aOR = 0.46; 95%CI: 0.22–0.97; aOR = 0.27; 95%CI: 0.12–0.60, respectively); women not aware of the pertussis vaccine campaign and with mid and low SES were less likely to be vaccinated, compared to those aware and with high SES (aOR = 0.15; 95%CI: 0.04–0.48; aOR = 0.05; 95%CI: 0.01–0.24, respectively). General practitioner (GP) recommendation was the main reason for receiving influenza vaccine (39.2%), and 71.8% of women were recommended pertussis vaccination from their GPs. The survey reports moderate uptake of vaccines among pregnant women, inequalities in uptake by SES and identifies GPs as primary source for vaccine recommendation. We recommend multifaceted campaigns, by engaging GPs, to target all socio-economic groups.